The Implementation Of Eating at Traditional Events Bakaua In Order To Preserve The Regional Culture Of Sijunjung District - Tama, Yuvran; Yelfi, Reno; Fridayati, Lucy; Zulfikar, Dikki (Universitas Negeri Padang, 2023)
The purpose of this study is to find out about the series of events, the execution of the meal, the equipment used for serving and processing as well as the symbolic and philosophical meaning of the dishes at the Bakaua Adat event. The type of research used was qualitative research. The research informants were Bundo Kanduang, Niniak Mamak, and the people in Nagari Koto Padang Ranah or Sijunjung Traditional Village who knew about Bakaua Adat events. The results of this study describe: 1) The series of Bakaua Adat Nagari Koto Padang Ranah or Sijunjung Traditional Villages of Sijunjung Regency such as: Niniak Mamak Meetings, Organizing traditional game competitions, Organizing alek nagari, Bajago-jago nights, and carrying out Bakaua Adat ceremonies (Praying and eating together or bajamba). 2) Types of food served, namely: Buffalo meat curry, lamang, white rice, godok bananas, crackers, bananas and kalio potatoes. 3) The equipment used consists of cooking and processing tools. Processing tools such as kitchen knives, millstones, stoves, frying pans, stale spoons and tablespoons. The serving utensils consist of: Dulang, serving lid, cloth, plastic and banana leaves. 4) The symbolic and philosophical meanings of the food served at the Bakaua Adat event are as follows: Buffalo meat curry (asking for rain), lamang (suluh nagari and kinship), rice (please help), crackers (complementary), kalio potato (complement each other), bananas (apology), boiled bananas (unanimous decision), water (tranquility). While the meaning of eating at the ceremony is to increase a sense of togetherness, hospitality, help and teach manners and norms in social life.